How do environmental policies affect green innovation and trade? Evidence from the WTO Environmental Database (EDB) - Francesco S. Bellelli; Ankai Xu (World Trade Organization (WTO), 2022)
This study investigates how environmental policies impact trade and innovation in environmental goods. We make two major contributions to the economic debate. First, we extract a set of information from the WTO Environmental Database (EDB) through natural language processing techniques that could be useful for future research and policy analysis. Second, we use this data to test a set of economic hypotheses on how environmental measures impact environmental innovation and trade. Our findings show that environmental measures can be an effective tool for stimulating green innovation and trade in green goods. However, policy design matters. Green innovation is most sensitive to R&D expenditure and measures on intellectual property protection and enforcement, whereas trade in green goods increases with environmental subsidies and support measures. Conversely, we find that non-tariff barriers - such as quarantine requirements, import quotas, regulation affecting movement or transit - reduce both imports and exports of environmental goods. Our findings also highlight strong path dependency in innovation. Hence, the earlier the intervention, the greater the accumulated benefits from green innovation. Conversely, delays in intervention increase the cost of transition by further "locking-in" the economy on dirtier exports and technologies. Finally, our result highlight that there is a clear linkage between innovation and trade. Past patents are a strong predictor of future exports, and nations tend to innovate more in technologies related to their exports. We also find evidence of strong technological spillovers across countries and sectors integrated in Global Value Chains (GVC). Hence, integration in environmental goods' GVCs could provide further channels of green technology diffusion and development.
Keywords: F14; F18; O38; Q55; Q58; 330; trade and environment; environmental policies; innovation